Inter- and Intra-Scanner Differences in Doppler Flow Measurements Using Three-Dimensional Printed Flow Phantom Model of the Carotid Artery in Preterm Infants. Issue 1 (2022) - Pereira, Sujith S.; Reeves, Jonathan; Birch, Malcolm; Ali, Ahmed S.; Sinha, Ajay K.; Kempley, Stephen T.
No abstract available